Achievement motivation in civics courses at vocational grammar schools. (April 2023) - Weisseno, Georg; Grobshäuser, Natalie
This article examines achievement motivation in connection with the political knowledge of upper secondary level pupils at german vocational grammar schools. The influence of achievement motivation in civic courses has been scarcely researched so far. In the expectancy-value model, expectations of success are important determinants of action in relation to academic achievements. Pupils' expectations of success or failure in civics courses have a behaviour-regulating function. They influence pupils' behaviour when learning about politics. In the cross-sectional survey of 470 pupils, results show lasting effects from an approach motivation ("hope of success") and an avoidance motivation ("fear of failure") studied. The data of this study confirmed the influence of achievement motivation in civics courses on the school-related political knowledge. While cultural capital makes no significant difference in the extent of the motivational constructs, a migrant background showed moderate but inconsistent effects and gender had clear negative effects for the girls. In this study, it was shown that based on the theoretical foundation described, the theory of domain-specific competency can be combined with the achievement motivation in Civics.